Poetic Language and the Emotion of Love in the Movie Dilan 1990: A Psycholinguistic Perspective - Amiril Achmed; Fitriyah Fitriyah (Journal of Social, Culture, and Language, 2026)
This study aims to analyze how the emotion of love affects the production of poetic language through a study of the character Dilan in the film Dilan 1990. With a descriptive qualitative approach and case study design, this research uses the film's dialogue as the main data which is analyzed thematically and psycholinguistically. Dilan's utterances full of metaphors, hyperbole, and personification are analyzed to reveal the relationship between emotional state and linguistic creativity. The findings show that love as the dominant emotion triggers complex brain activity-including activation of the limbic system, inferior frontal gyrus, and insula-which results in poetic and aesthetic language expressions. In addition, the use of novel and idiomatic metaphors in dialog also indicated the involvement of the right hemisphere and embodied cognition system, reinforcing that the emotion of love not only expresses feelings, but shapes cognitive structures and narrative memory in language. These results suggest that the interaction between emotions, brain and language in the context of Indonesian popular culture can be scientifically explained through psycholinguistic and affective neuroscience approaches.